Improving Students’ Reading Competence through DRTA ( Directed Reading Thinking Activity) Technique: A Classroom Action Research in the Seventh Semester Students of D-IV Midwifery Program of Health Sciences Faculty of Kadiri University 2015/2016 - Vitasmoro, Pamadya (English Education:Journal of English Teaching and Research, 2016)
The objectives of the research are to know whether DRTA technique can improve students’ reading competence or not, to know what are the students’ response to the DRTA technique and to evaluate the strengths and weakness of the DRTA technique when it is applied in teaching reading. The research was conducted in D-IV Midwifery Program of Health Sciences Faculty of Kadiri University August to November 2015. The subject of the research is the students of D-IV Midwifery students of Health Sciences Faculty of Kadiri University. The method of research is classroom action research and conducted in three cycles. Each cycle consists of planning, acting, observing, and reflecting. In collecting the data, the researcher collected both qualitative and quantitative data. To obtain the quantitative data the researcher administered the result of pre test and post tense. In finding the qualitative data, the researcher and collaborative teacher observed directly the teaching in the classroom, interviewed the teacher and students, did questionnaire and also used photograph. The quantitative data were analyzed using the mean score. Questionnaire data collected usually answer respondents frequency of items alternatives by Likert Scale and score scale for observation. The research findings show that DRTA technique is an appropriate technique which can improve student’s reading competence. First, DRTA can activate the students’ background knowledge related to the topic. Second, various activities in DRTA technique can enhance students’ confidence and motivation to have reading competence. Third, DRTA technique can guide the students to comprehend an overall description about the text. The improvement of reading competence can be seen from the result of pre- test which has the mean score 56.17, post test 1 is 67.11, post test 2 is 72.62 and post test 3 is 76.15. Some recommendations are made based on the research findings: (1) for English lecturer to use DRTA technique as one of alternative way of improving student’s reading competence (2) for the students to eliminate their fear of making mistakes in giving ideas and comprehending the passage Keywords : Reading Competence, DRTA Technique